Alkaloid and Phenolic Compounds of Rafflesia hasseltii Suringar and its host Tetrastigma leucostaphylum (Dennst.) Alston ex Mabb. in Bukit Tigapuluh National Park, Riau: A Preliminary Study - NERY SOFIYANTI; NINIK NIHAYATUL WAHIBAH; DEDEK PURWANTO; EDY SYAHPUTRA; KAMARUDIN MAT SALLEH (Society for Indonesian Biodiversity, 2008)
Two alkaloid compounds (nicotine and caffeine) together with three phenolic compounds (catechin, proanthocyanidin and phenolic acid) were firstly detected in Rafflesia hasseltii and its host, Tetrastigma leucostaphylum in Bukit Tigapuluh National Park, Riau. The content of all compounds is higher in R. hasseltii than its host.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Rafflesia hasseltii, Tetrastigma leucostaphylum, alkaloids, phenolic compounds, HPLC.